TERRORISM AS AN ASYMMETRIC WARFARE STRATEGY: THE CHECHEN WAR AND THE STRATEGIC ROLE OF SHAMIL BASAYEV - Muhamad Shamil Bashayev (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The Chechen War represents a paradigmatic case of asymmetric warfare in which terrorism was employed as a strategic instrument by non-state actors. This article examines terrorism not merely as ideological extremism, but as a coercive strategy shaped by structural power asymmetries between Chechen separatist groups and the Russian state. Using a qualitative historical approach combined with literature review and critical discourse analysis, the study analyzes the role of Shamil Basayev through the Budennovsk hostage crisis (1995) and the Kizlyar–Pervomayskoye attack (1996) as key turning points in the Chechen conflict. The findings demonstrate that terrorism functioned as an effective short-term tactic by generating political pressure and public attention, while simultaneously producing long-term strategic costs in the form of international delegitimization and intensified state repression. This article concludes that terrorism in asymmetric warfare exhibits a strategic paradox: it may be rational and effective in specific contexts, yet ultimately counterproductive to long-term political objectives.